Comparing perceived listening behavior differences between managers and nonmanagers living in the United States, India, and Malaysia - Roebuck, D. B.; Bell, Reginald L.; Raina, Reeta; Lee, Cheng Ean Catherine * (Sage, 2016)
Many managers and employees work in multinational organizations, but know little about what constitutes good or bad listening skills from a cross-cultural perspective. Little literature exists concerning the listening behaviors of managers and nonmanagers or the impact of national culture on listening skills. No clear understanding of what constitutes effective and ineffective listening across various cultures and organizational positions is known. Therefore, this study examines the listening skills of both managers and nonmanagers from India, the United States, and Malaysia. A total of 513 managers and nonmanagers from these countries completed a survey measuring self-perceptions of their engagement in four listening behaviors: distracted listening, empathetic listening, judgment rushing, and conclusion jumping. An analysis of variance procedure, with a 2 × 3 factorial design, was used to ascertain whether differences existed when each of the four derived factors was used one at a time as a dependent variable. The two independent variables were managers/nonmanagers and country of residence. The means differed on the main effects of managers/nonmanagers (p < .001) and country of residence (p < .001) and interaction between managers and nonmanagers across the United States, India, and Malaysia (p < .001) on all four factors. Therefore, perceptions of engaging in distracted listening, empathetic listening, judgment rushing, and conclusion jumping are different for managers and nonmanagers living in the United States, India, and Malaysia. This study’s findings will help both managers and nonmanagers from these countries understand the positives and negatives of these four listening practices and the influence of national culture on listening behaviors.